PERSPEKTIF MSDM PADA RESILIENSI OPERASIONAL: KAJIAN FENOMENOLOGI PENGAWASAN DAN KESELAMATAN KERJA - Sinaga, Irwan Nopian (Akademi Manajemen Informatika dan Komputer Widya Loka Medan, 2025)
This study aims to construct an operational resilience model through the lens of Human Resource Management (HRM) by integrating aspects of occupational safety and managerial supervision. Using a qualitative phenomenological design, this study explores the subjective experiences of 66 employees of PT. Rubber Hock Lie regarding the influence of the psychophysical environment and the effectiveness of competency development on performance stability. The findings indicate that sustainable productivity is a manifestation of harmony between the organization's technical and social systems (Socio-Technical Systems). The analysis identifies a disconnect between OHS infrastructure and the internalization of a safety culture due to repressive supervisory patterns. As a strategic solution, this study proposes a